A Short History of Copyright - Atkinson, Benedict. author. aut Link
VIII, 142 p.
Keywords: This book tells the story of how, over centuries, people, society and culture created laws affecting supply of information. In the 21st century, uniform global copyright laws are claimed to be indispensable to the success of entertainment, internet and other information industries. Do copyright laws encourage information flow? Many say that copyright laws limit dissemination, harming society. In the last 300 years, industries armed with copyrights controlled output and distribution. Now the internet’s disruption of economic patterns may radically reshape information regulation. Information freedom, a source of emancipation, may change the world.